The utilization of carbon dioxide by the microalgal species Scenedesmus - Daya, Trisha (Centre for Bioprocess Engineering Research, 2014)
Climate change, which is predominantly a result of anthropogenic global warming, is a major concern for humanity. The scientific consensus is that the rise of greenhouse gases, such as CO2, in the atmosphere has contributed to global warming. The increase in atmospheric CO2 is due to the burning of fossil fuels and deforestation. In South Africa, 77% of our primary energy needs are supplied by coal and our demand for energy is increasing. Cultivation of microalgae on flue gas from coal-fired plants and utilization of the algal biomass as an energy source has been proposed as a method for producing CO2-neutral fuels.